1996
DOI: 10.1046/j.1471-4159.1996.67052079.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Cyclic AMP Production by Carbamazepine

Abstract: The anticonvulsant carbamazepine is an effective treatment both for epilepsy and for bipolar affective disorder, but the molecular mechanism(s) underlying its therapeutic effects have not been identified. We have found that carbamazepine exerts significant inhibitory effects on the cyclic AMP (cAMP) generating system. Within the clinical therapeutic range (-~5Oj.tM), carbamazepine inhibited both basal and forskolin-stimulated cAMP production, without having any significant effects on phosphodiesterase activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 27 publications
(32 reference statements)
2
44
0
Order By: Relevance
“…The GHSR is also known to stimulate adenylyl cyclase [5]. Stimulation of adenylyl cyclase has been implicated in pro-convulsant effects [53][54][55][56][57]. Thus, one can theorize that GHSR desensitization/inverse agonism should result in anticonvulsant effects through inactivation of the CREB pathway, diminished IP 3 -dependent Ca 2+ release, and decreased adenylyl cyclase activity.…”
Section: Possible Downstream Molecular Pathways For Ghsr-mediated Antmentioning
confidence: 99%
“…The GHSR is also known to stimulate adenylyl cyclase [5]. Stimulation of adenylyl cyclase has been implicated in pro-convulsant effects [53][54][55][56][57]. Thus, one can theorize that GHSR desensitization/inverse agonism should result in anticonvulsant effects through inactivation of the CREB pathway, diminished IP 3 -dependent Ca 2+ release, and decreased adenylyl cyclase activity.…”
Section: Possible Downstream Molecular Pathways For Ghsr-mediated Antmentioning
confidence: 99%
“…As discussed in an earlier section, evidence suggests that carbamazepine may have direct inhibitory effects on adenylate cyclase [61], and in a number of studies has been shown to attenuate stimulated cyclic AMP signaling [54,[56][57][58][59]. This finding is especially interesting noting that lithium also attenuates stimulated cyclic AMP signaling [13].…”
Section: Carbamazepinementioning
confidence: 92%
“…Surprisingly, in spite of the mRNA changes, it has not been consistently found that lithium changes the total protein levels of G protein subunits. This evidence eventually led to studies suggesting that carbamazepine may directly inhibit adenylate cyclase [61]. Thus, Chen et al reported that at therapeutic concentrations carbamazepine inhibited both basal and stimulated cyclic AMP production [61].…”
Section: Lithiummentioning
confidence: 99%
See 2 more Smart Citations